Dietary fiber from burdock root ameliorates functional constipation in aging rats by regulating intestinal motility - Mo, Liya; Ma, Kaiyang; Li, Ying; Song, Jiangfeng; Song, Qiqi; Wang, Ling (Frontiers in Nutrition, 2025)
Functional constipation is a common gastrointestinal health issue among the aging population. Dietary fiber supplementation is widely recognized as a first-line strategy for constipation. However, the effectiveness of dietary fiber in practical applications remains unsatisfactory, and dietary fibers from different sources are believed to possess varying physiological activities in alleviating constipation. Burdock root is a vegetable rich in dietary fiber. In this study, loperamide was used to induce functional constipation in aged rats. Doses of 3 mg/kg·bw·day and 1.5 mg/kg·bw·day of dietary fiber from burdock root were used to intervene in functional constipation in aged rats. Research indicated that dietary fiber from burdock root enhanced intestinal motility to ameliorate functional constipation in aging rats. This effect may involve several mechanisms, including repairing the intestinal barrier, regulating intestinal hormones, and providing anti-inflammation and antioxidation. Our findings provide a theoretical basis for the potential mechanism by which burdock root dietary fiber can ameliorate functional constipation. It is expected to serve as a natural functional food to combat functional constipation in the aging population.